ASPEK RELIGIUSITAS NOVEL FATIMAH CHEN CHEN KARYA MOTINGGO BUSYE - Sujamo, Sujamo (ATAVISME, 2007)
Religiosity is the attitude, behavior, and insight of someone reflecting the quality of his/her personality. Religiosity is not only someone's knowledge about a religion, but also the value of the religion that he./sheapplied on his/her daily life in relation with The Almighty, other people, and nature. Religiosity is sometimes expressed in a literary work. As a literary work, a novel can also reveal religiosity through the characters' attitudes and behaviors in line with the plot of the novel. To understand the aspects of religiosity in a literary work, e.g. a novel, someone should read the work carefully and then reflect the characters' attitudes and behaviors in it referring to the values and rules of a religion related to the novel. Fatimah Chen Chen, a novel written by Motinggo Busye, is a kind of literary work that can be analyzed to find out the aspects of religiosity in it. Generally, they can be identified four aspects of religiosity in Fatimah Chen Chen, they are making a choice, being patient, being watchful, and being faithful.